INTERNATIONAL COMMISSION AGAINST IMPUNITY IN GUATEMALA: A NON-TRADITIONAL TRANSITIONAL JUSTICE EFFORT - Nyberg, Tove (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2015)
This paper examines the concept of transitional justice and makes the argument that transitional justice contexts would benefit from embracing a wider range of mechanisms. It uses the International Commission Against Impunity in Guatemala (CICIG) as an example of a non-traditional transitional justice measure and evaluates its mandate, set-up and achievements to show the advantages with a hybrid mechanism in the Guatemalan context.